A Study of the Effect of Circuit Training On the Explosive Leg Strength and Speed of the Players in the Game of Handball - Pravinbhai Ramjibhai Kharadi; Dr. Gandabhai Amthabhai Desai (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The purpose of this research study was to study the effect of Circuit training in handball on the Standing Broad Jump and Speed of players in the Game of Handball. This research study was limited to the inter-college players of H.N.G.U. Patan of Sabarkantha and Aravalli districts. Handball players were selected as the subjects in this research study. This research study was limited to students aged 18 to 25 years. In this research study, a total of 100 students were selected as subjects, 50 students in the circuit training group and 50 students in the control group. Explosive leg strength in the measurement scale was measured by the Standing Broad Jump test and speed was measured by the 50 yard desh run test. On the information obtained from the experimental group and the control group, validity was checked at level 0.05 by applying diffraction, covariance analysis (ANCOVA). The findings were as follows. The systematic 12-week Circuit training program showed a significant improvement in the Explosive leg strength and Speed of the selected subjects.